2018
DOI: 10.1111/tmi.13037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, antibiotic susceptibility pattern of bacterial isolates and factors associated with complications in culture‐proven typhoid patients admitted to an urban hospital in Bangladesh

Abstract: The high prevalence of typhoid fever among under-five children and complications among hospitalised patients are matters of concern. Sensitivity of Salmonella Typhi to ceftriaxone and cefixime was better than to other conventional antibiotics. Shorter duration of fever and thrombocytopenia on admission can be considered as early signs of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
(61 reference statements)
2
15
3
Order By: Relevance
“…Previous studies by Leung et al, Parry et al and Khatun et al had also demonstrated in their studies of similar risk factors in children with enteric fever predisposing for encephalopathy. 3,2 Currently dexamethasone is being used with clinical consensus worldwide for treatment of enteric encephalopathy and in present study, as well as previous studies by Qamar et al, Sagar V et al and Sejvar et al had demonstrated efficacy of dexamethasone in this condition. 4,8,9 The dose of dexamethasone used in enteric encephalopathy is high upto 1-2 mg/kg/day in divided doses, as mentioned previously by Chisti et al 6 Association of other complications like pneumonia and intestinal hemorrhage have been previously shown by Mellon et al 7 Khatun et al had previously shown that although the prevalence of MDR typhoid bacilli was not significantly high amongst those with encephalopathy, still nalidixic acid resistance is more common in those with encephalopathy and similar results were also found in present study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies by Leung et al, Parry et al and Khatun et al had also demonstrated in their studies of similar risk factors in children with enteric fever predisposing for encephalopathy. 3,2 Currently dexamethasone is being used with clinical consensus worldwide for treatment of enteric encephalopathy and in present study, as well as previous studies by Qamar et al, Sagar V et al and Sejvar et al had demonstrated efficacy of dexamethasone in this condition. 4,8,9 The dose of dexamethasone used in enteric encephalopathy is high upto 1-2 mg/kg/day in divided doses, as mentioned previously by Chisti et al 6 Association of other complications like pneumonia and intestinal hemorrhage have been previously shown by Mellon et al 7 Khatun et al had previously shown that although the prevalence of MDR typhoid bacilli was not significantly high amongst those with encephalopathy, still nalidixic acid resistance is more common in those with encephalopathy and similar results were also found in present study.…”
Section: Discussionsupporting
confidence: 83%
“…4,8,9 The dose of dexamethasone used in enteric encephalopathy is high upto 1-2 mg/kg/day in divided doses, as mentioned previously by Chisti et al 6 Association of other complications like pneumonia and intestinal hemorrhage have been previously shown by Mellon et al 7 Khatun et al had previously shown that although the prevalence of MDR typhoid bacilli was not significantly high amongst those with encephalopathy, still nalidixic acid resistance is more common in those with encephalopathy and similar results were also found in present study. 2…”
Section: Discussionmentioning
confidence: 99%
“…Khatun H et al reported 100% sensitivity of S. typhi to cefixime and ceftriaxone n 2018. 8 In contrast, we have found 14.5% resistance to cefixime and 6.6% resistance to ceftriaxone. Interestingly, 45 (59.2%) of our isolates of S. Typhi were sensitive to cotrimoxazole; this reemergence of susceptibility is probably due to the emergence of de novo susceptible strains or the loss of high molecular weight self-transmissible plasmids.…”
Section: Discussioncontrasting
confidence: 61%
“…Khatun H et al reported that, between 2010 to 2014, only 5 isolates of S. Typhi out of 431 in ICDDRB hospital, Dhaka, were resistant to azithromycin. 8 But, in recent years, clinicians do not consider azithromycin as a first line agent because of increasing resistance to azithromycin. Patel SR et al from Varanasi, India, reported azithromycin resistance in 21.3% cases in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Several literatures have described the relationship between duration of pre-hospital symptoms and risk of complications ( 6 , 22 ). A short period of fever and thrombocytopenia on admission may be the early signs of complications ( 23 , 24 ). Relative bradycardia may be a more common symptom in the early stages of uncomplicated typhoid fever ( 25 ).…”
Section: Discussionmentioning
confidence: 99%